THE CHANGING ROLE OF WORK ENVIRONMENT IN BALANCING WORKERS’ PERSONAL AND WORK LIFE - Tomaszewska-Lipiec, Renata (European Scientific Journal, ESJ, 2015)
The aim of the article is to consider the changing role of work environment in balancing workers’ personal and work life. This issue has been presented in the context of the idea of sustainable development and corporate social responsibility.